1993
DOI: 10.1161/01.cir.87.1.270
|View full text |Cite
|
Sign up to set email alerts
|

Tricarboxylic acid cycle activity in postischemic rat hearts.

Abstract: These results suggest that TCA cycle activity is not persistently decreased in dysfunctional reperfused myocardium after a brief ischemic episode and therefore cannot account for the reduced contractile function at that time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 51 publications
1
13
1
Order By: Relevance
“…Also, a source of acetyl-CoA other than pyruvate, either the medium chain fatty acid, octanoate, or the KB, AcAc, and BHB, was provided. Medium chain fatty acids is not subjected to carnitine palmitoyltransferase I regulation (41)(42)(43). Thus, the perfusate octanoate concentration sets the rate of mitochondrial acetyl-CoA generation.…”
Section: Resultsmentioning
confidence: 99%
“…Also, a source of acetyl-CoA other than pyruvate, either the medium chain fatty acid, octanoate, or the KB, AcAc, and BHB, was provided. Medium chain fatty acids is not subjected to carnitine palmitoyltransferase I regulation (41)(42)(43). Thus, the perfusate octanoate concentration sets the rate of mitochondrial acetyl-CoA generation.…”
Section: Resultsmentioning
confidence: 99%
“…It has been speculated that anaplerotic flux may serve as a biosensor between the cytoplasm and the mitochondria (11,36,39,43,48). Furthermore, evidence suggests a role for anaplerosis in the regulation of contractile function in the heart (15,23,30,42,49). Recent studies have also shown that flux through pyruvate carboxylase regulates amino acid synthesis (33,34) and may be important in controlling cell growth (34,43).…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in cardiac PCr/ATP with XOI is not likely due to an effect on infarct size because it is similar in control and infarcted hearts (Ref. 43, and see RESULTS) and because infarcted tissue does not contain significant PCr or ATP (45,48). XOI is one of the first metabolic interventions that normalize reduced cardiac energetics in any model of heart failure.…”
Section: Fig 1 Typical Transverse Short-axis 1 H Magnetic Resonancementioning
confidence: 94%
“…The PCr/ATP values were corrected for partial saturation effects using a factor determined in separate studies (6,8,46,47) that included fully relaxed acquisitions. Infarcted, nonviable myocardium lacks PCr and ATP (45,48). In prior 31 P MRS studies (16,18,19,32,33,37) of infarcted rodent hearts, the detected PCr and ATP signals were attributed to the surviving viable regions, even when the entire infarcted region was contained within the region studied by MRS. Based on this accepted practice and our efforts through animal positioning and slice selection to minimize infarcted tissue within the volume of interest, the cardiac PCr/ATP values reported here derive almost entirely from surviving, viable myocardium.…”
Section: In Micementioning
confidence: 97%